Implementation of an Evidence-Based Health Equity Curriculum for Reducing Implicit Bias at a Student-Run Free Clinic - Kapil Gururangan; Charisma Hooda; Lars Osterberg (Journal of Student-Run Clinics, 2021)
Healthcare providers’ implicit biases negatively impact the quality of patient care. Education to promote bias awareness is the first step to mitigating this negative effect. Implicit bias education is particularly relevant to volunteers at student-run free clinics, where patients often belong to underserved populations who are most vulnerable to providers’ implicit bias. No prior studies have reported the development and evaluation of an implicit bias curriculum in this setting. We developed an evidence-based health equity curriculum for undergraduate student volunteers at a student-run free clinic and report preliminary results of a pilot study. The training program was regarded as highly informative and relevant to clinical practice by students, and their qualitative feedback was organized thematically. Our data suggest that volunteers experienced increases in empathy after participating in this implicit bias training, despite not demonstrating a significant change in implicit biases. Further study of educational interventions to modify unconscious bias and provider empathy is warranted to augment the efficacy of these interventions and their benefit to patient care.